Methodology of Organizing Music Lessons in 5-7 Grades of General Secondary Schools Based on New Technologies - Abdumutalibovich, Ma’rufjon Ashurov (Jurnal Teknologi Pendidikan, 2024)
In this article, the methodology of the music teacher's organization of music lessons in the 5th-7th grades of general secondary schools on the basis of new technologies is explained. This comprehensive exploration emphasizes the significance of an individualized teaching approach in music pedagogy, focusing on tailoring education to each student's unique needs, interests, and abilities. The method involves conducting individual diagnoses, employing diverse teaching methods, incorporating musical preferences, adapting to learning paces, and providing additional resources. The main part delves into the importance of lesson planning, goal setting, assessing student progress, interactive teaching, and fostering support and motivation. It emphasizes diverse activities within lessons to stimulate interest and underscores the importance of an individualized approach.